Consequences of the World-scale Crisis for the Labour Market of the European Union - Stawicka, Magdalena Kinga (Konsekwencje światowego kryzysu gospodarczego dla rynku pracy Unii Europejskiej, 2010)
The European Union means nearly half a billion of inhabitants residing in twenty seven member states. From 2006 there has been a tendency to decrease the unemployment rate there. Therefore, the unemployment rate which was 8.2% in 2006, was decreased to the level of 7.1% in 2007 and 7.0% in 2008. In 2009 there was an increase in the unemployment rate in all member states of the European Union but its scale was different in particular states. In Baltic states as well as in Ireland and Spain one could observe the highest growth in the unemployment rate in a year-scale (6-10%), whereas in Belgium, Germany, Luxemburg and Holland the increase of this rate did not exceed the value of 1%.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 201-209
Keywords: unemployment rate; number of employed persons; labour market; European Union